Interplay between oxytocin and sensory systems in the orchestration of socio-emotional behaviors - Grinevich, Valéry; Stoop, Ron (Neuron, 2018)
The neuropeptide oxytocin (OT) attracts the interest of neuroscientists, psychologists, and psychiatrists due to its capacity to modulate emotional and social behavior. Although much has been published on the effects of OT on brain regions and mechanisms at the core of these processes, its role in sensory processing, so important for detecting social context with sufficient accuracy and sensitivity, has been much less studied. In the present review, we summarize evidence for OT modulation of sensory processing and, conversely, effects of sensory input on endogenous OT signaling. We concentrate on mammals, aiming to provide a systematic analysis of the current knowledge on this reciprocal regulation and the role it may play in social and emotional behaviors.
Gesehen am 15.05.2019